(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
Abstract This research aims to To investigate the most common grammatical errors made by using Google Translate in translating narrative text and to explore the students’ perception in translating in narrative text using google translate first semester of english education at Universitas Muslim Indonesia. The research method is qualitative method conducted at the first Semester English Education study program at Universitas Muslim Indonesia. The total sample were 12 students. The research instrument employed were grammar test and questionnaire. The data were analysed based on the type of error made by students. some types of error made by student in using google translate. Those errors were of omission,misformation, misordering and addiction.